Repairing an inguinal hernia under local anesthesia and sedation - سليمان جمال (Latakia University Journal -Medical Sciences Series, 2024)
introduction: Hernias are one of the most common conditions seen in inpatients and outpatients, but the exact incidence is still unknown, estimated at approximately 5% of the population during their lifetime. Inguinal hernias are the most common hernias seen in patients, accounting for about 75% of all hernias, and about two-thirds of them are of the indirect type. Inguinal hernia repair constitutes an important percentage of the total number of elective and emergency surgeries performed in hospitals around the world. Surgery is usually performed under general anesthesia, but it may be difficult or not possible in some cases, especially in elderly patients or those with comorbidities that raise the proportion of anesthetic complications, which precludes the possibility of the procedure. The importance and purpose of the research: The possibility of performing inguinal hernia repair under local anesthesia and sedation when general anesthesia is not available or difficult to perform in patients who suffer from intubation difficulties or wish to perform surgery under local anesthesia due to their fear of general anesthesia. Research method: A retrospective study was conducted that included 90 patients who attended the Department of General Surgery at Tishreen University Hospital between April 2022 and March 2023 with an inguinal hernia that needed surgical repair. The surgical procedure was performed under local anesthesia and sedation with ketofol (2 ml ketamine + 10 ml propofol).